Outcomes of Autologous Stem Cell Transplantation (ASCT) in Relapsed/Refractory Germ Cell Tumors: Single Center Experience from Turkey - Yildiz, Fatih; Durnali, Ayse; Eraslan, Emrah; Ilhan, Aysegul; Tufan, Gulnihal; Aslan, Ferit; Arslan, Ulku Yalcintas; Alkis, Necati; Demirci, Umut; Altuntas, Fevzi; et al. (Urology Journal, 2020)
Purpose: Germ cell tumors (GCTs) are rare and highly curable malignancies. However, salvage treatments for relapsed or refractory disease are needed in approximately 20-60% of the patients. As salvage therapy, autologous stem cell transplantation (ASCT) administered after high-dose chemotherapy (HDCT) may be a feasible option as well as standard dose chemotherapy (SDCT). This study aimed to evaluate the efficacy and toxicity of ASCT in salvage therapy of GCTs retrospectively. Materials and Methods: Male patients older than 18 years of age who underwent ASCT due to a relapsed/refractory GCT were included in the study. Results: The median age of 18 patients included in the study was 28 (19-46). The majority of patients (n:16, 88.8%) had non-seminomatous GCT histology. All of the patients had relapsed or refractory GCTs and received bleomycin, etoposide, cisplatin (BEP) combination therapy previously. Half of the patients were in the poor risk group. ASCT was administered as a second-line therapy in 14 (77.7%) patients and third-line therapy in four (22.2%) patients. There is no ASCT-related exitus. Febrile neutropenia (FN) developed in almost all patients. Complete response (CR) was obtained in 7 (38.8%) patients, partial response (PR) in four (22.2%) patients after ASCT. The 2-year PFS was 44.4% and the median PFS was 8.7 (2.7-12.6) months. Median OS was 22.7 (3.9-41.7) months and 3 years OS was 50.0%. Conclusion: In conclusion, ASCT was found to be an effective and safe treatment option in salvage therapy of GCT patients in our study.